Pengembangan Learning Management System Dengan Model Project-Based Learning Untuk Pembelajaran Basis Data - Cintiya Cintiya; Martini Dwi Endah Susanti (CV. SINAR HOWUHOWU, 2026)
The learning process at SMKN 4 Bojonegoro faces challenges, namely the lack of digital infrastructure and learning that is still centered on teachers. Students and teachers have difficulty managing learning documents, both materials and assignments. Thus, a learning management system with a project-based learning model is needed that can be used in the learning process. This research aims to develop a learning management system with a project-based learning model that can help students, teachers and admins in managing learning in the classroom. The learning management system is developed based on moodle with a project-based learning model. Moodle-based LMS is integrated with the code runner plugin. Code runner plugins can help students practice coding without having to install additional software. The subject of this study is a software engineering student in class XI of SMK Negeri 4 Bojonegoro. This research uses the Research and Development (R&D) method with the ADDIE (analyze, design, development, implementation, evaluation) model. Feasibility test of moodle-based learning management system with a project-based learning model using blackbox testing and expert validation tests. The blackbox test on this LMS got valid results and the expert validation test got a very valid category.